Large dentigerous cyst associated with the maxillary impacted supernumerary teeth: A rare occurrence and literature review - Noriaki Aoki; Megumi Matumoto; Soichiro Ishii; Yasuaki Okuma; Himiko Umezawa; Junichi Baba; Takaaki Ito (Tabriz University of Medical Sciences, 2022)
Dentigerous cysts are common odontogenic cysts of the jaw but are rarely associated with supernumerary teeth. Few cases of large dentigerous cysts associated with anterior maxillary supernumerary teeth have been reported. The English literature has documented only four cases of dentigerous cysts>40 mm in diameter associated with supernumerary teeth. A 47-year-old man was referred to our hospital, complaining of minor pain in the maxillary gingiva. Computed tomography revealed a well-defined oval unilocular radiolucent lesion (50×45×35 mm) in the right maxilla, including two impacted supernumerary teeth. A dentigerous cyst associated with impacted anterior maxillary supernumerary teeth was diagnosed. The two impacted teeth were surgically removed, and the cyst was enucleated using the Caldwell-Luc approach. Histopathology confirmed the diagnosis of a large dentigerous cyst associated with impacted anterior maxillary supernumerary teeth. The postoperative course has been uneventful for two years. We also reviewed the relevant English literature.